Management of Acute Coronary Syndromes During the Coronavirus Disease 2019 Pandemic: Deviations from Guidelines and Pragmatic Considerations for Patients and Healthcare Workers - Henry Seligman (Radcliffe Medical Media, 2020)
Coronavirus disease 2019 (COVID-19) is forcing cardiology departments to rapidly adapt existing clinical guidelines to a new reality and this is especially the case for acute coronary syndrome pathways. In this focused review, the authors discuss how COVID-19 is affecting acute cardiology care and propose pragmatic guideline modifications for the diagnosis and management of acute coronary syndrome patients, particularly around the appropriateness of invasive strategies as well as length of hospital stay. The authors also discuss the use of personal protective equipment for healthcare workers in cardiology. Based on shared global experiences and growing peer-reviewed literature, it is possible to put in place modified acute coronary syndrome treatment pathways to offer safe pragmatic decisions to patients and staff.